Absence of Trichinella spiralis in swine carcasses slaughtered in the midwestern Region of Paraná State, Brazil - Siqueira, Amanda Keller [UNESP]; Da Silva, Vanessa Gomes; Ferro, Isabelle Dangui; Freitas, Ricardo Antonio; Giesel, Alexandre (Universidade Estadual de Londrina, 2020)
Trichinella spiralis causes severe infections in humans, resulting in various clinical symptoms and even death, in several countries worldwide. Human trichinellosis has been reported in 55 countries, and mainly affects certain ethnic groups and tourists. It is caused by the ingestion of raw, undercooked meat or pork, or their by-products containing parasitic larvae. Infections in swine especially occur due to the parasitic contamination of flood containing animal products, predation by rodents and other animals infected with T. spiralis, and due to the frequent habit of cannibalism in intensive production systems. This study aimed to evaluate the prevalence of T. spiralis in pig carcasses from a slaughterhouse located in the midwestern region of Paraná State, Brazil. Pools of 100 g of diaphragm, containing at least 1 g of tissue from each test animal, were collected, ground, and subjected to acid digestion with pepsin (1:10,000) and 25% hydrochloric acid. Sampling was performed in accordance to the methodology recommended by the European Union. All the 735, 902 samples collected between 2010 and 2013, and in 2018, were negative for Trichinella spp. larvae. The pigs came from 483 farms from 90 municipalities from the three states of southern Brazil (Paraná, Santa Catarina and Rio Grande do Sul). The absence of the parasite in different animal species, reported by surveys conducted in Brazil, could confirm the country as free from trichinellosis. Although T. spiralis is not endemic to Brazil, it is necessary to subject the meat of adult pigs slaughtered here and exported to other countries to inspections and parasitological examinations. It is therefore necessary to continually inspect pig carcasses for T. spiralis in slaughterhouses worldwide.
Keywords: Inspection; Meat trade; Nematode; Trichinellosis